Entrepreneurial Culture and the Education System: The Case of Moroccan Universities - Asli Amina; Abdelaziz Zohri (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
Despite the growing number of education programs and training seminars that aim at forging entrepreneurial skills, the question whether entrepreneurship is an innate talent or a skill that can be learned has persisted for years and still shapes debates among educators, students and practitioners as well. It has often been believed that the spirit and capacity of entrepreneurship depend on traits inherent in the character and a psychological predisposition to take risks. However, from the 80s onward, this vision has boldly been questioned and it has been suggested that entrepreneurship can also be learned. Several authors (Drucker, 1985, Shane & Venkataraman, 2001, Eckhardt & Johnson, 2011, Wiklund, Davidsson, Audretsch & Karlsson, 2011) have argued that entrepreneurship is more of an attitude, a technique, a practice, and a discipline that can be taught and strengthened particularly through higher education and globally via the education system. Developing an entrepreneurial culture and mindset has nowadays become a very popular idea all over the world, and has been considered a leverage for economic, social and societal development. However, the question that needs to be raised here relates to how can entrepreneurship be taught and developed and what have countries' education systems, especially in the developing world, been doing to build entrepreneurs and encourage entrepreneurial endeavors? To shed some light on these questions, this paper focuses on the role of the educational system of a country in the development of the entrepreneurial culture and is particularly interested in the case of Morocco. It aims at investigating whether the educational system contributes to developing the learners' entrepreneurial skills and fostering an entrepreneurship mindset. This paper will also try to examine the extent to which adopted pedagogies meet the needs and requirement globally established for developing entrepreneurship within individual learners.
Keywords: 650; Entrepreneurship; entrepreneurial culture; entrepreneurial spirit; higher education; pedagogy; Morocco